Organocatalytic Enantioselective Assembly of Spirooxindole‐naphthopyrans through Tandem Friedel–Crafts Type/Hemiketalization. Issue 9 (21st April 2016) - Muthusamy, Subramaniam; Prakash, Muthuraj; Ramakrishnan, Chandrasekaran; Gromiha, M. Michael; Kesavan, Venkitasamy
Abstract: A new synthetic strategy to construct spirooxindole‐naphthopyran scaffold has been demonstrated via Friedel–Crafts type/hemiketalization of oxindole α‐ketoester with 2‐naphthol. Under the established reaction condition, quaternary chiral center at C3‐position of oxindole has been created with very good asymmetric induction up to 98 % for a broad range of substrates. DFT calculations, which account for the stereochemical outcome, were performed. Abstract : Purely organic : A facile organocatalytic protocol for the construction of spirooxindole encompassing the naphthopyran ring system is employed by using bifunctional thiourea from proline as the catalyst. Various substituents of the oxindole ring and substitutions either at C6‐ or C7‐position of 2‐naphthol are well accommodated under the stabilized conditions.